FINTECH ANALYSIS OF QRIS PAYMENT TRANSACTIONS USING TAM METHOD IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) IN BANGLI, BALI - Kadek Linda Kusumayani; A.A. Istri Ita Paramitha; Linda Yupita (Jurnal TAM (Technology Acceptance Model), 2023)
The presence of Financial Technology (Fintech), Quick Response Code Indonesian Standard (QRIS), provides changes to payment transactions that used to be conventional but have now turned digital. With this research, it is intended to find out what influences users use of Fintech services, especially QRIS in Bangli, by applying the original Technology Acceptance Model (TAM) method, which is modified using one external variable. This study uses quantitative methods and uses Partial Least squares (PLS) with the help of Smart-PLS 3.0 software. The results of the Inner Model Q2 Evaluation Test have a value of 84.1%. This shows that the acceptance of QRIS service user interest (Behavior Intention) can be explained by the variables Perceived Risk on Perceived Usefulness, Perceived Ease of Use, and Attitude Toward Using, and there are six hypotheses that are accepted.